PHYSICOCHEMICAL CHANGES OF DWARF BANANA (Musa acuminata) DURING VACUUM PACKAGING STORAGE - David Septian Sumanto Marpaung; Dwi Cahyani; Ni Wayan Arya Utari; Anggia Indriyani; Resa Apriliani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Banana is tropical fruit contain health nutrition and fiber. Dwarf banana is one of type banana that well growth in Indonesia, particularly in Lampung Province. However, its economic value become exported commodities is limited by its short shelf life. In this study, the physicochemical changes were observed under vacuum packaging storage, in order to know the potency of vacuum packaging to prolong the shelf life of dwarf banana. The results showed that the vacuum packaging could reduce weight loss compare to other treatments. The maintenance of green color by vacuum packaging was also showed positive result. Furthermore, the dwarf banana under vacuum packaging storage was also showed lowest TSS, in other words, the dwarf maturity could be delayed. These results suggested the vacuum packaging could be used as potential packaging for dwarf banana Keywords: dwarf banana, vacuum packaging, postharvest, physicochemical properties